Answer:
![x=\pm\sqrt{77n+53}](https://tex.z-dn.net/?f=x%3D%5Cpm%5Csqrt%7B77n%2B53%7D)
Step-by-step explanation:
We have been given an equivalence equation
. We are asked to find all the square root of the given equivalence equation.
Upon converting our given equivalence equation into an equation, we will get:
Add 53 on both sides:
![x^2-53+53=77n+53](https://tex.z-dn.net/?f=x%5E2-53%2B53%3D77n%2B53)
![x^2=77n+53](https://tex.z-dn.net/?f=x%5E2%3D77n%2B53)
Take square root of both sides:
![x=\pm\sqrt{77n+53}](https://tex.z-dn.net/?f=x%3D%5Cpm%5Csqrt%7B77n%2B53%7D)
Therefore, the square root for our given equation would be
.
Answer: correct answer is B
Step-by-step explanation: I know this because for example if you run one mile it will take you less time than it would if you walked 1 mile
The sum of the angles equals 540
There are 3 angles that measure (x - 30) and 2 angles that measure (x)
3(x - 30) + 2(x) = 540
3x - 90 + 2x = 540
5x - 90 = 540
5x = 630
x = 126
x - 30 = 126 - 30 = 96
Answer: x = 126, x-30 = 96
Since all the sides add up to 10x+2, that means that 10x-2-<side1>-<side2>=<side3>. Plugging it in, we have 10x-2-5x-(2x+9)=side3, and 5x-2-(2x+9)=side3, then expanding it to 5x-2-2x-9=3x-11=side3
Answer:
it is not clear pls resend it fasttt